Finance and Development, June 2008. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2008)
The June 2008 issue tackles the crisis in financial markets in industrial countries from a number of angles. Articles look at the origins of the crisis in the subprime mortgage market in the United States and track its spillover into other markets. Then authors examine what can be done to prevent future crises. Other articles look at bank capital adequacy rules and Basel II, whether emerging markets and industrial economies are decoupling or converging, capital flows to low-income countries, efforts to achieve the MDGs, and currency intervention. Back to Basics looks at over-the-counter (OTC) markets and the People in Economics column profiles Jacques Polak. Picture This is on the digital divide.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet